Integración de las tic como recurso didáctico en el proceso de enseñanza aprendizaje, de la unidad temática la diversidad natural, de la asignatura de ciencias naturales, para el quinto grado de educación general básica, de la unidad educativa Adolfo Valarezo periodo lectivo 2016-2017 - Minga Quezada, Gabriela del Cisne (2018)
This thesis refers to the integration of TIC as a didactic resource to contribute to the improvement of the teaching-learning process, the thematic unit "Natural diversity", the subject of natural sciences, for the fifth grade of general basic education, Of the Educational Unit "Adolfo Valarezo", academic period 2016-2017. The educational unit "Adolfo Valarezo" is a fiscal institution, secular and mixed, that provides a quality education. However, this institution does not have TIC -based didactic resources that allow teachers to apply to their classes to improve the Teaching Learning Process especially in subjects with a high theoretical content such as the subject of Natural Sciences. This is why the need to integrate TIC as a didactic resource to contribute to the improvement of the teaching-learning process, from the thematic unit "Natural diversity", of the subject of natural sciences, to the fifth grade of basic general education, Of the Educational Unit "Adolfo Valarezo", academic period 2016-2017. For the development of this research was based on the scientific method through the application of data collection instruments such as interviews, questionnaires, observation sheets and cognitive tests. For the integration of TIC in the PEA, a didactic resource based on TIC (multimedia) was selected according to the needs of the fifth grade students of EGB and a methodology was proposed in which parts of the multimedia were taken to introduce them in the Class combined with the explanation of the teacher, this methodology was developed during 6 classes of the natural science subject in the unit "Natural diversity", product of which was obtained a reinforcement in the learnings of the students which Was tested through the application of a cognitive test.